Palliative care in paediatric oncology: perceptions, expertise and practices from the perspective of the multidisciplinary team - Adriana Ferreira da Silva; Helena Becker Issi; Maria da Graça Corso da Motta; Daisy Zanchi de Abreu Botene
OBJECTIVE: To reveal the perceptions, expertise and practices of multi-professional teams providing palliative care to children in a paediatric oncology unit. The research questions were based on everyday care, facilitations and difficulties, essential aspects of professional approaches, and the inter-disciplinary focus of care for children in palliative care and their families. METHOD: Qualitative, exploratory and descriptive research. Data were collected from June to October 2013 from nine professional multidisciplinary team members by means of a semi-structured interview submitted to thematic analysis. RESULTS: The following four themes emerged from analysis: palliative care: conceptions of the multi-professional team; the construction of singular care; the facilitations and difficulties experienced by the team and significant lessons learned. CONCLUSIONS: The subjects revealed that the team also suffers with the death of a child and, like the family, moves toward the construction of coping mechanisms for the elaboration of mourning. Paradoxically, the team shares knowledge to determine the foundations of a singular therapeutic project and inserts the family in this process so that it can be the protagonist of the child's care.